2018
DOI: 10.1038/s41598-018-35646-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding flow dynamics, viability and metastatic potency of cervical cancer (HeLa) cells through constricted microchannel

Abstract: To understand the burgeoning challenges of metastasis, a microchannel of 35 μm diameter, constricted to 7 μm for a distance of 200 μm in a total length of 3 mm, was designed and fabricated using a mask aligner made of polydimethylsiloxane (PDMS) to mimic in vivo capillaries. A thin glass cover-slide was mounted on top to monitor the motion of single or aggregated malignant HeLa cells (size 17–30 μm) microscopically through the constricted microchannel at a constant flow rate of 30 μl/h. Quantitative deconvolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…As mentioned previously, the microchannel consisted of several obstructions, and the cells passing through the channel underwent deformation and pronounced morphological changes, decreasing the percentage of viable cells at the outlet [20]. Mesenchymal transformed MDA-MB-468 cells were collected by trypsinization before starting the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned previously, the microchannel consisted of several obstructions, and the cells passing through the channel underwent deformation and pronounced morphological changes, decreasing the percentage of viable cells at the outlet [20]. Mesenchymal transformed MDA-MB-468 cells were collected by trypsinization before starting the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, "clasmatosis", or cytoplasmic fragmentation, a phenomenon that has been confirmed to attract specific populations of immune cells, thereby mediating the efficiency of the metastatic cell seeding, 42 could be observed in cells transiting narrow capillaries. 5 Long-term effects of constrictions on cell fate Sophisticated in vivo experiments, 16,17,42 together with the development of microfluidic platforms, 9,19,20,27,43 have shown how capillary constriction might affect cell fate. Constricted microchannels mimicking capillary constriction forces have been reported to reduce cancer cell viability by 50% upon exit.…”
Section: Arrest In Capillaries and Mechanical Deformationmentioning
confidence: 99%
“…For instance, while migration of cancer cells in the tumour stroma is thought to be directed by chemoattractant gradients, 15 the migration of cancer cells in capillaries is controlled by fluid forces. 16,17 Consequently, the migration of cancer cells through micronsized pores or capillary constrictions that mimic the extracellular matrix (ECM) can take hours, 18,19 whereas, when physiological blood flow rates are applied to comparable constrictions, cancer cells are able to overcome them within milliseconds or seconds, 9,20,21 showing that capillary transit occurs at a faster rate than migration through 3D microenvironments. These substantial differences in the rates of migration between the tumour microenvironment and capillaries might affect the dynamics of acquired adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…14 Nath et al flowed HeLa cells across 7 µm-wide constrictions, and demonstrated that cell viability was reduced by 50%, but that the expression of MMP2, a metalloproteinase involved in stromal tissue degradation, was unchanged. 15 In a very interesting study, Xia et al flowed leucocytes, MDA-MB-231 and MCF-7 cell lines into arrays of pores. 16 They reported a pressure dependence of the deformation of cells and nuclei, and proposed that such studies could guide the optimization of CTC sorting devices.…”
Section: Introductionmentioning
confidence: 99%